Work Readiness of Select Graduating Students of Mindanao State University Iligan Institute of Technology - D. MANALA-O, SAFA; J. Manulat Sr., Rhede Nelson (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
. As thousands of students graduate each year, many lind chemselvos unemployed because of skills gaps that aro brought about by low work roadiness levels. Work readinass is defined as the collection of soft and hard skills that employers require from job applicants to be employod in a spocific Gold. Literature claims that skills gap is a rosult of a variety of inherent factors in students and a failuro to establish links between schools and companios to prepare studonts with the right skills set currently domanded in the workplaco. In rosponso, chis papor studied the work roadinass lovels of select graduating students Crom Mindanao State University - Iligan Institute of Tochnolog (MSU-IIT) to investigate the prosenco of skills gaps with respoct to the gradunting students’ profile, and tho relationship between such gups, and the ethnicity and ser of the graduating students. Findings roveal that there are significant differences in tho required and perceived workreadiness levels of all Business Management graduating students, including Visayan, Moro, malo and female, but not for any of the Computer Studios graduating students. The findings also establish a relationship between the differences noted for all graduating student’s sampled and their ethnicity. Results show that Visayan graduating student tend to have smaller difference’s or skills gaps, thus, have higher work readiness levels, than Moro graduating students.